SOME INTEGRAL CURVES ASSOCIATED WITH A TIMELIKE FRENET CURVE IN MINKOWSKI 3-SPACE - Duldul, Bahar Uyar (HONAM MATHEMATICAL SOC, 2017)
In this paper, we give some relations related with a spacelike principal-direction curve and a spacelike binormal-direction curve of a timelike Frenet curve. The Darboux-direction curve and the Darboux-rectifying curve of a timelike Frenet curve in Minkowski 3-space E-1(3) are introduced and some characterizations related with these associated curves are given. Later we define the spacelike V-direction curve which is associated with a timelike curve lying on a timelike oriented surface in E-1(3) and present some results together with the relationships between the curvatures of this associated curve.
Keywords: timelike Frenet curve; associated curve; integral curve; slant helix; rectifying curve; POSITION VECTOR; SLANT HELICES; Mathematics